2017
DOI: 10.1016/j.hrtlng.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of palliative care service consultation in a sample of critically ill ICU patients at high risk of dying

Abstract: Objective Describe patterns of palliative care service consultation among a sample of ICU patients at high risk of dying. Background Patients receiving mechanical ventilation (MV) face threats to comfort, social connectedness and dignity due to pain, heavy sedation and physical restraint. Palliative care consultation services may mitigate poor outcomes. Methods From a dataset of 1440 ICU patients with ≥2 days of MV and ≥12 hours of sustained wakefulness, we identified those at high risk of dying and/or who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…45 In this review, conversations continue to be late and infrequent. 46 Future studies should aim to capture the effects of palliative care conversations on surrogate decision-makers during initial stages of an admission. There were differences between what the clinician attempted to communicate and what the surrogate understood.…”
Section: Discussionmentioning
confidence: 99%
“…45 In this review, conversations continue to be late and infrequent. 46 Future studies should aim to capture the effects of palliative care conversations on surrogate decision-makers during initial stages of an admission. There were differences between what the clinician attempted to communicate and what the surrogate understood.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven physical therapists participated in the study. To ensure their anonymity, the study participants were identified with a reference code beginning with PT (physical therapist) followed by a number representing the order in which they were interviewed (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Methodsmentioning
confidence: 99%
“…1 Nevertheless, despite this, when assistance reports to patients in palliative care (PC), there is a lot of contradiction concerning the conduct to be performed, in the face of complex questions regarding threats to the patient's comfort and dignity. 2,3 Therefore, it is necessary to discuss ways to promote care for palliative patients and their families. 4 Despite the changes in the panorama of assistance to patients in PC, there is still a theoretical gap regarding the understanding and perception of physiotherapists concerning the concept and their professional skills in the face of the needs of patients in internal PC in an ICU.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the intensive care unit (ICU), many PC needs are apparent including: communication of prognosis and diagnosis; complex patient, family and surrogate interactions; difficult decision making and goals-of-care (GOC) conversations; complex symptom management; and end-of-life (EOL) care often involving withdrawal of interventions. 2,3 Despite estimates that a large subset of ICU patients would benefit from PC consultation, 4 specialty PC remains underutilized in the ICU setting overall 5 and for the subset of patients who die in the ICU. 6 PC interventions in the critically ill have been associated with reduced subsequent ICU admissions and reduced ICU length of stay.…”
Section: Introductionmentioning
confidence: 99%